Liquid polymeric membrane composition of ion selective electrode based on thiazole-4-carboxamide as ionophore - Jamil N.W.Z.; Yahya M.Z.A.; Jumal J.; Kasim N.A.M. (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS